A new braided model of the Amulet Amplatzer for accurate simulations of left atrial appendage occlusion procedures - Md, Rafizul Islam; Lee, Matthew T.; Cook, Andrew C.; Weir-McCall, Jonathan; Martin, Claire A.; Peach, Thomas W.; Burriesci, Gaetano; Bosi, Giorgia M. (Computers in biology and medicine, 2025)
Atrial Fibrillation (AF) is a cardiac disease altering the human heart rate. It is posing an increasing burden to society, with complications that lead to stroke and ischemic events from thromboembolisms, originating in the left atrial appendage (LAA). Percutaneous LAA occlusion (LAAO) is becoming an increasingly adopted preventive treatment option due to its minimally invasive nature. However, this treatment faces complex challenges: the heterogeneity of LAA morphologies limits the pre-operative planning and several procedures are associated with peri-device leakage from malposition and device-related thrombi. One of the two most commonly deployed LAAO devices (LAAODs) is the Amulet Amplatzer (AA), a mesh-like pacifier device. In-silico models have demonstrated their potential to serve as supporting tools for clinical planning, providing insight able to enhance the efficacy and safety of the intervention. Most of the computational studies approximate the AA to a closed surface model. In this work, we aimed to develop a more realistic and detailed structural model of the AA, capturing the mesh of wires. Experimental tests on the physical device were conducted to compare the behaviour of simplified closed surface models and the newly developed braided geometry. The results have demonstrated how closed surface models of the AA fail to capture the real deformation mechanism of the physical device. Conversely, the more realistic braided characterisation mimics more closely the changes in shape of the physical AA, by capturing the change in angles of the wires. Finally, the virtual deployment of the intertwined model into a patient-specific LAA resulted in a configuration similar to the clinically implanted AA. •Structural computational modelling can support clinical LAAO procedures.•Braided and closed surface geometries of the Amulet Amplatzer were recreated.•Experimental tests were performed to validate the virtual models.•Braided model mimics more closely the deformation of the physical Amulet Amplatzer.•Patient-specific virtual LAAO closely matches the device shape derived from clinical images.